Motives and Objectives of the Application of Benchmarking in Air Transport - Lot Polish Airlines S. A. Case Study - Gierczak-Korzeniowska, Beata (Studia Oeconomica Posnaniensia, 2016)
The main aim of this article is to present the motives and objectives of the application of benchmarking in air transport. Although the literature does not lack a theoretical justification for the reasons for the implementation of benchmarking in companies, the specifics of the industry, such as the aviation industry, and its limited access for security reasons of the airlines or their passengers, make the results cognitively significant. Studies conducted in LOT Polish Airlines to identify the motives of the application of the method include the specifics and nature of each department whose employees were included in the study. The article also mentions that correct identification of the objectives and motives of the use of benchmarking can have a significant impact on the development of the company and, above all, is an expression of skilful positioning of the company in the realities of the market. The study used a questionnaire method and the method of standardized survey interview, which was limited only to the managers of individual departments. The aim of the interview was to refine and clarify the data from the surveys. When analyzing and interpreting the results, the elements of descriptive statistics and statistical inference were used. The results showed that airlines do not differ significantly from other companies in determining motives of the application of benchmarking. However, astonishingly, in defining the reasons for the implementation of the method, which is demanding in terms of time and cost, there was no identification of factors associated with innovation, development and research, and learning and acquiring information, which are undoubtedly valuable for this transport sector.